Pengaruh Net Profit Margin, Likuiditas dan Pertumbuhan Penjualan terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Keumala Hayati; Antonius KAP Simbolon; Sonya Situmorang; Iyuslina Haloho; Iman Kristiani Tafonao (Politeknik Ganesha Medan, 2019)
This research was conducted to test whether net profit margin, liquidity, and sales growth significantly influence stock price in manufacturing companies in 2013-2017. The population in this study are all manufacturing companies listed on the indonesia stock exchange. The sampling technique used is purposive sampling. Selected sample in certain criteria as many as 36 manufacturing companies listed on the IDX. The analytical method used is multiple linear regression through the SPSS version 23.0. in this study the effect is only the net profit margin variable that has a significant effect on stock price.